2017
DOI: 10.1200/jco.2017.72.5465
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sexual Orientation and Overall and Site-Specific Diagnosis of Cancer: Evidence From Two National Patient Surveys in England

Abstract: PurposeTo address gaps in evidence on the risk of cancer in people from sexual minorities.Patients and MethodsWe used data from 796,594 population-based English General Practice Patient Survey responders to explore the prevalence of self-reported diagnoses of cancer in the last 5 years among sexual minorities compared with heterosexual women and men. We analyzed data from 249,010 hospital-based English Cancer Patient Experience Survey responders with sexual orientation as a binary outcome, and International Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 36 publications
3
39
0
2
Order By: Relevance
“…A UK study of cancer showed higher rates of cancer diagnosis in the last 5 years in gay and bisexual male general practitioner (GP) patients compared to heterosexual men, but no difference in cancer diagnosis rates overall in lesbian and bisexual women compared to heterosexual women (Saunders et al 2017). The higher rates of cancer in gay and bisexual men were likely due to higher HIV/AIDS infection rates.…”
Section: Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…A UK study of cancer showed higher rates of cancer diagnosis in the last 5 years in gay and bisexual male general practitioner (GP) patients compared to heterosexual men, but no difference in cancer diagnosis rates overall in lesbian and bisexual women compared to heterosexual women (Saunders et al 2017). The higher rates of cancer in gay and bisexual men were likely due to higher HIV/AIDS infection rates.…”
Section: Cancermentioning
confidence: 99%
“…Gay or bisexual men were overrepresented among men with Kaposi's sarcoma and anal and penile cancer. (Saunders et al 2017). Lesbian or bisexual women were overrepresented among women with oropharyngeal cancer (Saunders et al 2017).…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Data regarding the management of lymphoma in HIV negative sexual minority patients is significantly lacking and is often limited to case reports. As a result of increased association of HIV and lifestyle factors such as smoking and alcohol use noted in various studies, most of what is known or extrapolated to the LGBTI community and malignancy is based older studies of HIV-associated malignancies (36,37). Frisch et al evaluated the association of sexual orientation and malignancy and determined an increased incidence of NHL, as well as anal cancer and Kaposi sarcoma among homosexual men (38).…”
Section: Methodsmentioning
confidence: 99%
“…This sex-ratio is mainly explained by the higher HPV transmission for vaginal-oral rather than penile-oral sexual intercourse. Saunders et al recently showed that risk of OPC was higher in women having sex with women compared with heterosexual women, although this association was not found in men having sex with men, in agreement with a higher risk of HPV transmission by vaginal- vs. penile-oral sex [ 60 ]. The lower risk of HPV-induced OPC observed in women could also be partly explained by the higher immunity acquired by women due to more frequent exposure to HPV in the genital mucosa and by a still little understood role of the combined exposure to HPV and tobacco that is generally stronger in men than women [ 59 ].…”
Section: Introductionmentioning
confidence: 99%